الضغط النفسي لدى المرأة العاملة دراسة ميدانية على عينة من الموظفات في قطاع التربية ببلدية المقرن - بليلة, ريم (University of Eloued جامعة الوادي, 2023)
ملخص الدراسة: هدفت دراستنا إلى الكشف عن فروق مستوى الضغط النفسي لدى المرأة العاملة في قطاع التعليم، وقد اقترح إجراء الدراسة على عينة قومها 52عاملة من مقاطعة التربوية (ابتدائي، متوسط، ثانوي) بالمقرن ولاية الوادي وقد اعتمدنا المنهج الوصفي المقارن لتحقيق أهداف الدراسة الحالية، وكانت أداة جمع البيانات في هذه الدراسة استبانه بحث مكونة من 30 بند تقيس الضغط النفسي وتم التأكد من الخصائص السيكومترية لتطبيقها. وخلصت الدراسة إلى النتائج التالية: - توجد فروق في مستوى الضغط النفسي لدى أفراد عينة الدراسة حسب متغير الحالة الاجتماعية. - توجد فروق في مستوى الضغط النفسي لدى أفراد عينة الدراسة حسب متغير موطن العمل. - توجد فروق في مستوى الضغط النفسي لدى أفراد عينة الدراسة حسب متغير نوع السكن.   Abstract: Our study aimed to reveal the level of psychological stress among women working in the education sector. It was suggested that the study be conducted on a sample of 52 female workers from the educational district (primary, intermediate, secondary) in MAGRAN,EL-oued state. We have adopted the descriptive approach to achieve the objectives of the current study. The data collection tool was in This study is a research questionnaire consisting of 30 items that measure psychological stress, and the psychometric properties of its application were confirmed. The study concluded the following results: - There are differences in the level of psychological stress among the study sample, according to the social status variable. - There are differences in the level of psychological stress among the study sample, according to the workplace variable. - There are differences in the level of psychological stress among the study sample according to the housing type variable.
تخصص علم نفس